Economic burden of cardiorespiratory hospitalizations associated with respiratory syncytial virus among United States adults in 2017-2019 - Deesha A Patel; Zachary A Marcum; Aisara Chansakul; Astra Toyip; Katherine Nerney; Catherine A Panozzo; Samantha St Laurent; Darshan Mehta; Parinaz Ghaswalla (Taylor & Francis Group, 2024)
Morbidity and mortality caused by respiratory syncytial virus (RSV) in older adults and those with underlying health conditions can be potentially alleviated through vaccination. To assist vaccine policy decision-makers and payers, we estimated the annual economic burden of RSV-associated cardiorespiratory hospitalizations among insured US adults aged ≥18 y in the Merative MarketScan claims database from September through August of 2017-2018 and 2018-2019. Negative binomial regression models were used to estimate the number of RSV-associated cardiorespiratory hospitalizations using MarketScan-identified cardiorespiratory diagnosis codes in the presence or absence of RSV circulation per weekly laboratory test positivity percentages from the Centers for Disease Control and Prevention. This number was multiplied by mean cardiorespiratory hospitalization costs to estimate total costs for RSV-associated cardiorespiratory hospitalizations. Number and cost for International Classification of Diseases (ICD)-coded RSV hospitalizations were quantified from MarketScan. In 2017-2018 and 2018-2019, respectively, 18,515,878 and 16,462,120 adults with commercial or Medicare supplemental benefits were assessed. In 2017-2018, 301,248 cardiorespiratory hospitalizations were observed; 0.32% had RSV-specific ICD codes, costing $44,916,324, and 5.52% were RSV-associated cardiorespiratory hospitalizations, costing $734,078,602 (95% CI: $460,826,580-$1,103,358,799). In 2018-2019, 215,525 cardiorespiratory hospitalizations were observed; 0.34% had RSV-specific ICD codes, costing $33,053,105, and 3.14% were RSV-associated cardiorespiratory hospitalizations, costing $287,549,472 (95% CI: $173,377,778-$421,884,259). RSV contributes to substantial economic burden of cardiorespiratory hospitalizations among US adults. Modeling excess risk using viral positivity data provides a comprehensive estimation of RSV hospitalization burden and associated costs, compared with relying on ICD diagnosis codes alone.